2020
DOI: 10.3390/en13020379
|View full text |Cite
|
Sign up to set email alerts
|

Feedstock-Dependent Phosphate Recovery in a Pilot-Scale Hydrothermal Liquefaction Bio-Crude Production

Abstract: Microalgae (Spirulina) and primary sewage sludge are considerable feedstocks for future fuel-producing biorefinery. These feedstocks have either a high fuel production potential (algae) or a particularly high appearance as waste (sludge). Both feedstocks bring high loads of nutrients (P, N) that must be addressed in sound biorefinery concepts that primarily target specific hydrocarbons, such as liquid fuels. Hydrothermal liquefaction (HTL), which produces bio-crude oil that is ready for catalytic upgrading (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 86 publications
(121 reference statements)
1
38
0
Order By: Relevance
“…One study found that oxalic and sulfuric acids can effectively extract P from hydrochar with 80-95% of P leached, but no further precipitation of solid fertilizer was conducted (Acelas et al, 2014). Several studies have performed struvite production with acidic leachate from hydrochar and ammonium-rich HTP aqueous phase (320-2,970 mg/L) (Becker et al, 2019;Ovsyannikova et al, 2020;Zhai et al, 2014b). A high P recovery rate (82-98%) can be reached in batch scales.…”
Section: ==========================mentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that oxalic and sulfuric acids can effectively extract P from hydrochar with 80-95% of P leached, but no further precipitation of solid fertilizer was conducted (Acelas et al, 2014). Several studies have performed struvite production with acidic leachate from hydrochar and ammonium-rich HTP aqueous phase (320-2,970 mg/L) (Becker et al, 2019;Ovsyannikova et al, 2020;Zhai et al, 2014b). A high P recovery rate (82-98%) can be reached in batch scales.…”
Section: ==========================mentioning
confidence: 99%
“…The low overall recovery rate was attributed to the dispersion of P-containing particles into the biocrude (Ovsyannikova et al, 2020).…”
Section: ==========================mentioning
confidence: 99%
“…Research on the liquid fraction of digestates has rapidly intensified in recent years, covering struvite recovery [15], ammonia stripping, vacuum evaporation [16], and microalgae or duckweed cultivation [17]. The research primarily focuses on determining the effectiveness of particular recovery processes [18][19][20]. It is necessary, however, to valorise and assess their suitability, including the fertiliser value of the recovered products, e.g., struvite or ammonium sulphate.…”
Section: Introductionmentioning
confidence: 99%
“…The major proportion of P present in the biomass was recovered in the solid phase in all cases. With the introduction of the alkali catalysts, the concentration of multivalent metal ions (e.g., Ca 2+ , Al 3+ , Fe 2+/3+ ) in the solid phase increased, which led to the higher concentration of P in the form of phosphate salts in the same phase [57,58]. Based on the results presented in Table 4, the molar ratio of Ca/P in the solid residue is 1.3 to 2.4, which, in most cases, meets the required amount of Ca to form hydroxyapatite.…”
Section: Inorganic Element Distributionmentioning
confidence: 99%